(untitled) (Ágora Journal, 2024)
This article discusses Brazilian modernism through dance and music, highlighting Villa-Lobos’s contribution to scenic dance from the first tour of the Ballets Russes in Brazil in 1913 to the 1960s. Using primarily newspaper articles from the Villa-Lobos museum collection, the dynamics of Brazilian ballet will be examined, a belated reflection of the modernization of this genre by Diaghilev’s Ballets Russes, in which Villa-Lobos was involved, emphasizing the opportunities that this scenario offered for his composition and international recognition. These national ballets presented at the Municipal Theater of Rio de Janeiro contributed to the formation of a national imaginary and to the legacy of modernism. It will also be demonstrated how his collaboration with renowned Russian choreographers brought a new expression to national identity and artistic trends. Thus, this research reveals a choreographic wealth and relevant artistic projects that deserve to be revisited today.